Managing genital infection in community family planning clinics: an alternative approach to holistic sexual health service provision. Issue 2 (30th March 2004) - Evans, J; Baraitser, P; Cross, J; Bacon, L; Piper, J
Abstract : Objective: To pilot and evaluate sexually transmitted infection (STI) management in community family planning clinics (FPCs). Methods: Number of STI tests taken, positive results, infections treated, contacts traced/treated, referrals to specialist services and time from testing to treatment were documented as well as age and sex of the population tested. Results: STI tests taken increased from 233 to 308/month and male clients seen increased from 114 to 147/month across all clinics. Chlamydia prevalence rates in one large clinic increased from 6.7% to 11.9%. 82% of those with STIs in this clinic were treated. Of 44 clients treated for chlamydia, 84% had partner notification performed, 0.43 contacts were treated for every client with chlamydia and referrals to specialist services decreased. 70% of STIs were detected in clinic users under the age of 25 and 45.5% of clients tested under the age of 16 had an STI. Before STI treatment was available at FP clinics 52% of clients with STIs attended specialist services after referral and time from testing to treatment was 19 days. Managing STIs in the community increased treatment rates to 82% with a testing to treatment time of 10 days. Conclusions: The management of uncomplicated genital infection in community FPCs working in partnership with specialist services is a feasible and effective approach to holistic sexual health service provision.